Haemorrhage into an arachnoid cyst: a serious complication of minor head trauma. Issue 4 (1st July 2002) - De, K; Berry, K; Denniston, S
Abstract : Arachnoid cysts are infra-arachnoidal cerebrospinal fluid collections that are usually asymptomatic. However, they can become acutely symptomatic because of haemorrhage and cyst enlargement, which may result from minor head trauma. The range of symptoms is wide and many are "soft" signs. Diagnosis is important as cysts causing mass effect require surgery. A case is reported of a child presenting with localised headaches after minor head trauma. Computed tomography demonstrated an arachnoid cyst with evidence of haemorrhage, which required surgical intervention. Other cases of arachnoid cyst presenting to our hospital or reported in the literature are reviewed with respect to presenting symptoms and signs. Localised headaches, behavioural or cognitive changes and ataxia are more commonly associated with this disorder than nausea, vomiting, visual disturbances or seizures. This range of symptomatology following minor head trauma may warrant computed tomography when other criteria for this investigation are not met.